Prevalence of Ocular Morbidity Among Road Traffic Accident Patients and its Management at a Tertiary Care Centre - Kafle, Prerna Arjyal; Chaudhary, Neha Priyadarshani; Goyal, Nancy (Journal of Nepalgunj Medical College, 2025)
Introduction: Road traffic accidents are a significant cause of preventable ocular morbidity. They can lead to permanent visual impairment and reduction in quality of life. Aims: To determine the prevalence, clinical spectrum, and management of ocular injuries among RTA patients presenting to a tertiary care center in Nepal. Methods: A hospital-based observational cross-sectional study was conducted at Birat Medical College Teaching Hospital. A total of 278 patients presenting with road traffic accidents were enrolled through consecutive sampling. Comprehensive ophthalmic examination was performed for all patients, and ocular injuries were classified based on standard trauma classifications. Statistical analysis was performed to see the associations between variables. Results: Ocular involvement was detected in 19.1%. Male predominance (65.5%) was recorded. Two-wheeler riders constituted 66.5% of road traffic accidents victims and 77.36% of those with ocular injuries. Those with ocular injuries 66.03% were not using helmets, and alcohol intake was reported in 53.8%. Periocular injuries were the most common (65%). A significant association was observed between nature of travel and ocular injury (p = 0.0002), and between mode of accident and ocular involvement (p = 0.0000). At presentation, 71.7% of patients had normal visual acuity, and most were managed conservatively. Conclusion: Ocular injuries represent a significant yet preventable consequence of road traffic accidents. Strengthening road safety regulations, promoting helmet use, and ensuring early ophthalmic evaluation are essential to reduce RTA-related ocular morbidity.